Efficiency and Cost Studies of Hinteregger all Terrain Skyline Crane in West Bengal - Mitra, S. K.; Sood, K. G. (Indian Forester, 1976)
The potentially valuable hill forests of Darjeellng District in West Bengal remained unexploited because of poor communication and transport facilities. With the introduction of modern logging equipments like gravity conveyor, All Terrain Skyline Crane, Lasso winches etc. the extraction of timber is now economically feasible from the inaccessible hilly areas. The efficiency and cost studies is conducted on Hinteregger All Terrain Skyline Crane at Dhapar in Mo block of Kalimpong Forest Division, The cost of transportation of wood per cu. metre for the span of 450 metres is calculated and found to be Rs. 36.68. The study has revealed that the machine is not being used at its full load capacity; the cost of transportation would have been much lower had the machine been worked at its rated capacity.